Organic Kale and Cereal Rye Grain Production Following a Sunn Hemp Cover Crop - Ted S. Kornecki; Kipling S. Balkcom (Agronomy, 2020)
A four-year field experiment was initiated in 2011 at the EV. Smith Research Station, in central Alabama, to determine the effect of sunn hemp (Crotalaria juncea L.) termination methods on organically grown kale (Brassica oleracea, var. acephala L.) for fresh market and cereal rye (Secale cereale L.) for grain. Three different termination methods for the sunn hemp cover crop were chosen: (1) rolling/crimping with an experimental two-stage roller/crimper, (2) rotary mowing, and (3) rotary mowing with incorporation (disking). Kale plots were harvested in the winter and rye plots were harvested in the following spring. Kale plots were fallow from January to June (kept mowed) until planting sunn hemp again across all plots in late spring of the next growing season. Over four growing seasons, average sunn hemp biomass (dry basis) was 10,981 kg ha−1 with plant height of 2.4 m. The average C/N ratio of sunn hemp was 23:1. Sunn hemp biomass amounts differed among growing seasons (from 5589 to 14,720 kg ha−1) due to different weather conditions. Kale yield also varied across growing seasons, with the highest yield of 17,565 kg ha−1 measured in 2012 and the lowest (3915 kg ha−1) in 2014 due to massive weed pressure. Generally, sunn hemp residue management affected kale yield, with greater yields measured for mowed and incorporated residue (15,054 kg ha−1) compared with lower yields for mowed (6758 kg ha−1) and rolled sunn hemp (5559 kg ha−1). Lower yields were related to poor kale seed-to-soil contact (hair pinning) from large amounts of sunn hemp residue on the soil surface. Over four growing seasons, cereal rye grain yield varied among growing seasons, with an average yield of 1358 kg ha−1. Moreover, sunn hemp residue treatments affected grain yield, with greater yields for rolled (1419 kg ha−1) and mowed residue (1467 kg ha−1) compared with a lower yield (1187 kg ha−1) for mowed and incorporated sunn hemp residue.